Achieving patient safety goals through enhancing legal knowledge and comprehensive disclosure policies - Jahn Kassim, Puteri Nemie (SciTechnol, 2019)
The changing legal landscapes in judicial approaches in preferring patient-centred approaches as the benchmark for good medical practices has subsequently increase the medical profession’s legal obligations towards their patients. The medical profession is constantly expected to adhere to the demands of patient autonomy and rights of self-determination in various aspects of medical care. Thus, in achieving patient safety goals which emphasises on “safe medical practices as well as minimising risks of harm to patients”, the medical profession should always keep abreast with the legal developments that are affecting their practice. Knowledge of these legal developments will eventually prepare them to handle medico-legal issues and eventually, reduce the likelihood of court litigation. Further, lawsuits can also be alleviated through “effective communication” which is also amongst the main goals of patient safety. The promotion of ‘open-disclosure’ policies and honest communication will encourage reconciliation, strengthen doctor-patient relationship and ultimately, safeguard public trust in the medical profession. Nevertheless, ‘open-disclosure’ policies which one of the key ingredients includes “making apologies or expressions of regret” must be developed in tandem with a comprehensive legal framework that shields those making apologies from legal liability. Thus, the enhancement of legal knowledge coupled with effective disclosure policies are crucial in overcoming the impending barriers towards the achievement of patient safety goals in the modern healthcare setting.